Dorsal root ganglion stimulation produces differential effects on action potential propagation across a population of biophysically distinct C-neurons - Graham, Robert D.; Jhand, Amolak S.; Lempka, Scott F. (Frontiers in Pain Research, 2022)
Dorsal root ganglion stimulation (DRGS) is a neurostimulation therapy used to manage chronic pain that does not respond to conventional therapies. Unfortunately, not all patients receive sufficient pain relief from DRGS, leaving them with few other treatment options. Presently, our understanding of the mechanisms of action of DRGS is incomplete, preventing us from determining why some patients do not receive analgesia from the therapy. One hypothesis suggests that DRGS augments the filtering of action potentials (APs) at the T-junction of nociceptive C-neurons. To test this hypothesis, we utilized a computational modeling approach in which we developed a population of one thousand biophysically distinct C-neuron models which each produced electrophysiological characteristics (e.g., AP height, AP duration) reported in previous experimental studies. We used this population of model C-neurons to study how morphological and electrophysiological characteristics affected the propagation of APs through the T-junction. We found that trains of APs can propagate through the T-junction in the orthodromic direction at a higher frequency than in the antidromic direction due to the decrease in axonal diameter from the peripheral to spinal axon. Including slow outward conductances in the axonal compartments near the T-junction reduced following frequencies to ranges measured experimentally. We next used the population of C-neuron models to investigate how DRGS affected the orthodromic propagation of APs through the T-junction. Our data suggest that suprathreshold DRGS augmented the filtering of APs at the T-junction of some model C-neurons while increasing the activity of other model C-neurons. However, the stimulus pulse amplitudes required to induce activity in C-neurons (i.e., several mA) fell outside the range of stimulation pulse amplitudes used clinically (i.e., typically ≤ 1 mA). Furthermore, our data suggest that somatic GABA currents activated directly or indirectly by the DRGS pulse may produce diverse effects on orthodromic AP propagation in C-neurons. These data suggest DRGS may produce differential effects across a population of C-neurons and indicate that understanding how inherent biological variability affects a neuron’s response to therapeutic electrical stimulation may be helpful in understanding its mechanisms of action.